Assets, Activities and Rural Income Generation: Evidence from a Multicountry Analysis - Winters, P.; Davis, B.; Carletto, G.; Covarrubias, K.; Quinones, E. J.; Zezza, A.; Azzarri, C.; Stamoulis, K. (2012)
This paper examines the links between the assets and the economic activities of rural households in developing countries to provide insight into how the promotion of certain key assets-particularly education, land, and infrastructure-influences the economic choices of these households. Nationally representative data from 15 countries which form part of the rural income-generating activities (RIGA) database are used in the analysis. The results indicate that improved land access is linked to agricultural production and thus will lead households to take, on average, this path for improving household welfare. Higher levels of education and greater access to infrastructure appear to be most closely linked to non-agricultural wage employment. (C) 2009 Elsevier Ltd. All rights reserved.